Direct versus Indirect Remedies for Externalities - Green, Jerry; Sheshinski, Eytan (Journal of Political Economy, 1976)
This paper is concerned with tax policies designed to obtain an improved competitive allocation in the presence of consumption externalities. It is known that the full optimum can, in general, be attained only through the imposition of excise taxes at different levels for different individuals. Since these may be ruled out (possibly because of implementation costs), one is confined to consider second-best taxes. The common interpretation of the Pigouvian principle has called for taxes on the externality-creating commodities. With no relationships between the consumption of different commodities the Pigouvian principle is obviously impeccable. But the existence of substitutes or complements for an externality-causing commodity raises the possibility of indirect policies: treating the externality through the markets for related goods. Obviously, if the direct policy is not feasible, the indirect treatment may provide some partial remedy. We show, however, that even when direct policies are available, the overall optimum may involve only indirect policies. An example with such a result is provided in the paper. We also list a number of cases in which the traditional prescription is confirmed, and the overall optimum involves only direct policies.